2020
DOI: 10.48550/arxiv.2007.09493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep Hough-Transform Line Priors

Abstract: Classical work on line segment detection is knowledge-based; it uses carefully designed geometric priors using either image gradients, pixel groupings, or Hough transform variants. Instead, current deep learning methods do away with all prior knowledge and replace priors by training deep networks on large manually annotated datasets. Here, we reduce the dependency on labeled data by building on the classic knowledge-based priors while using deep networks to learn features. We add line priors through a trainabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
(122 reference statements)
0
5
0
Order By: Relevance
“…The results from our experiment demonstrated that the proposed approach is feasible to detect both plant and line positions with high accuracy. Moreover, the comparison of our method against [ 44 , 45 ] deep neural networks indicated that our method could return accurate results, better than those of the state-of-the-art, and, when compared against its baseline (Visual Features), an improvement from 0.907 to 0.951 occurred. As such, we intend to discuss here this improvement and the importance of graphs theory in conjunction with the DNN model.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The results from our experiment demonstrated that the proposed approach is feasible to detect both plant and line positions with high accuracy. Moreover, the comparison of our method against [ 44 , 45 ] deep neural networks indicated that our method could return accurate results, better than those of the state-of-the-art, and, when compared against its baseline (Visual Features), an improvement from 0.907 to 0.951 occurred. As such, we intend to discuss here this improvement and the importance of graphs theory in conjunction with the DNN model.…”
Section: Discussionmentioning
confidence: 87%
“…The proposed method was compared with two recent state-of-the-art methods in Table 4 . Deep Hough Transform [ 44 ] integrated the classical Hough transform into deeply learned representations, obtaining promising results in line detection using public datasets. PPGNet [ 45 ] is like the proposed method since it models the problem as a graph.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in a very similar paper [19], authors use the sequence of Hough Transform, several convolutions and an inverse Hough Transforms as a part of their network for pixel-based segmentation of straight line segments. From the perspective of a general-purpose line detection, the dataset used to train and test the network -Wireframe [16] is inconsistent, as some clearly salient straight lines are absent from the desired answer (see images below).…”
Section: Related Researchmentioning
confidence: 99%
“…From the perspective of a general-purpose line detection, the dataset used to train and test the network -Wireframe [16] is inconsistent, as some clearly salient straight lines are absent from the desired answer (see images below). We believe that the CNN proposed in [19] spends many parameters to distinguish between "important" and "unimportant" lines and, possibly, overfits to the dataset strongly.…”
Section: Related Researchmentioning
confidence: 99%